Aluminium tolerance in the tropical leguminous N2-fixing shrub Acaciella angustissima (Mill.) Britton & Rose inoculated with Sinorhizobium mexicanum Tolerancia al aluminio en la leguminosa arbustiva tropical fijadora de N2 Acaciella angustissima (Mill.) Britton & Rose inoculada con Sinorhizobium mexicanum - REINER RINCÓN-ROSALES (Universidad de Concepción, 2011)
The tropical legume Acaciella angustissima inoculated with or without Sinorhizobium mexicanum ITTG R7T strain was cultivated in an aluminium (Al) spiked soil to study its tolerance towards this metal. Seedlings of A. angustissima were grown in soil with 0, 2, 4 or 6 mg Al kg-1. The effect of Al and inoculation on growth, nodulation, and nitrogen and tannins content in the plants was monitored. Height and total and dry root weight of plantlets decreased significantly when soil was spiked with Al, but increased when inoculated. Al decreased the number of nodules. Inoculum increased total N and tannin content of the plantlets. It was found that Al reduced the growth of the tropical leguminous N2-fixing shrub A. angustissima, while inoculation with S. mexicanum ITTG R7T stimulated its growth and increased its tannin and N content. La leguminosa tropical Acaciella angustissima inoculada con o sin la cepa Sinorhizobium mexicanum ITTG R7T fue cultivada en un suelo tratado con (Al) para estudiar la tolerancia a este metal. Las plantas de A. angustissima fueron crecidas en el suelo con 0, 2, 4 y 6 mg de Al kg-1. Se hizo un seguimiento del efecto de Al e inoculación en el crecimiento, la nodulación, el contenido de nitrogeno y el contenido de taninos en las plantas. La altura, el peso seco total y el peso seco de la raíz de las plantas decrementó significativamente cuando el suelo fue tratado con Al, pero incrementó cuando fue inoculado. El Al disminuyó el número de nódulos. El inóculo incrementó el N total y el contenido de taninos de las plantas. En este experimento fue encontrado que el Al reduce el crecimiento de la leguminosa arbustiva tropical fijadora de N2 A. angustissima, mientras la inoculación con S. mexicanum ITTG R7T estimula el crecimiento e incrementa el contenido de taninos y nitrógeno.